STRATEGI KOMUNIKASI HUMAS (PUSH, PULL DAN PASS) DALAM MEMBANGUN CITRA PERUSAHAAN PELINDO SUB REGIONAL JAWA (The Commercium, 2023)
This research aims to determine how the Public Relat/ions Communication Strategy of Pelindo Sub Regional Java builds the company's image. This is a descriptive qualitative research using a case study method. The descriptive method uses qualitative research with a qualitative approach to produce a systematic explanation and description of the company's activities, namely CSR. Data collection is obtained through observation and in-depth snowball interviews. The results of this study show that Pelindo Sub Regional Java builds its image through CSR activities in Surabaya City through SMEs and Environmental Development. Pelindo Sub Regional Java also uses a public relations communication strategy through the company's social media. Social media plays an important role in the publication process of every company's activities, especially CSR, in building the company's image through Instagram social media.